Financial Distress Analysis Using Altman, Springate, Zmijewski on Textile Company PT Sri Rejeki Isman Tbk. - Munandar, Irwansyah; Natasya; Maiyaliza (Al Tijarah, 2025)
Indonesia's textile industry, which includes the production of fibers, yarns, fabrics, and clothing, has long been the backbone of the country's economy, contributing jobs and foreign exchange through exports. In its heyday in the 1980s, the industry was thriving, but in recent decades, it has faced significant setbacks due to inefficient management, global competition and unfavorable trade policies. Many textile factories have gone out of business, including PT Sri Rejeki Isman Tbk (Sritex), which despite nearly 50 years of experience, is now debt-ridden and struggling to survive. This study goal is to forecast a company’s financial health. The method used in this study uses data as its data source and is descriptive quantitative in nature. The findings indicated that the company could face financial difficulties, because in the 2021-2023 range the company experienced losses and experienced an increase in debt because it could not pay debts at maturity.